Reading into Soundscapes: Between Ma and Concretization - Jestrovic, Siljiva (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2016)
This essay explores the role of the listener/participant in the process of shaping sound works. I consider factors both internal to the works’ structures and inner dynamics, as well as external to them, and how they are determined by ever shifting parameters of context within which they are received. The analysis revolves around two very different artistic works : Takeshi Kosugi’s audio-visual installation Mano Dharma, electronic (1967), exhibited at the IKON Gallery in Birmingham in September 2015, and Between, an immersive performance piece that uses the audio-walk as its main strategy, created by Theatre Studies students at the University of Warwick in June 2015. My approach to these works relies on the assumption of a semiotic impulse which imposes itself as the urge to engage the process of meaning making, followed by the strategy I propose as ideally suited to the interpretation of these works, a process I call reading-into .Reading-into is proposed variably as both a deliberate phenomenological strategy and a form of involuntary imposition of the semiotic impulse to ask the following questions : What are the possibilities and limits of the listener/participant’s reading-into ? How does reading-into relate to existing theoretical frameworks concerning aesthetic reception? What are the elements within and without the work itself that shape the process of reading-into ? How do unreadable elements of the work which resist semiotization shape our modes of engagement?